Constantes de Movimento para o Modelo Sinh-Gordon Supersimétrico N = 1 com Defeito - Spano, Nathaly Infantini [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
From the generators of the Kac-Moody superálgebra 's TIL'l(2,1) write the Lax pair for the supersymmetric sinh-Gordon model. In addition, we ?nd that through the zero curvature obtained the Lax equation reproduces the equations of motion of the model. For the analysis of defective theories calculated by means of a gauge transformation, the default matrix for the model sinh supersymetric Gordon, and present the result similar to the sine-Gordon model. We also note that in the defect region, the ?eld equations of the theory obey the type of Backlund transformations. The energy and momentum for the super sinh-Gordon model were also obtained from a general expression that allows us to obtain the in?nite set of conserved charges for style. In addition, the contributions of the defect these quantities have also been found

A partir dos geradores da superágebra de Kac-Moody 's TIL'l(2,1) escrevemos o par de Lax para o modelo sinh-Gordon supersimétrico. Em adição, veri?camos que através da equação de curvatura nula o Lax obtido, reproduz as equações de movimento do modelo. Para a análise de teorias com defeito calculamos, por meio de uma transformação de Gauge, a matriz de defeito para o modelo sinh-Gordon supersimétrico, e apresentamos o resultado similar obtido para o modelo sine-Gordon. Notamos ainda que na região do defeito, os campos da teoria obedecem equações do tipo das tranformações de Backlund. Foram obtidas também a energia e o momento para o modelo super sinh-Gordon, a partir de uma expressão geral, que nos permite obter o conjunto in?nito de cargas conservadas para modelo. Além disso, as contribuições do defeito dessas quantidades foram também encontradas
Keywords: Supersimetria; Equações integrais; Lei da conservação (Fisica); Backlund, Transformações de